Motorized Wheelbarrow - Mohammad Noor, Hafsa; Azman, Muhammad Fahmi; Nordim, Nor Farah Amira; Mohamed, Norfarhana; Ismail, Suhairi; Khairol Hisam Hamran, (Multidisciplinary Applied Research and Innovation, 2021)
Wheelbarrow is a small cart with a single wheel at the front and two supporting legs and two handles at the rear, used typically for carrying loads in building work or gardening. The use of wheelbarrow especially in construction field is one of the important elements to ensure the ease of construction work. However, the wheelbarrow functionality on the market today uses a manual method which is worker have to lift handle at the wheelbarrow and move it to somewhere else. This method takes a longer time to finish a work, worker need more work energy when lifting the wheelbarrow that full with load to another place. Worker need tool and equipment that can be used to help the construction work process easily, quickly and effectively. A motorized wheelbarrow had been fabricated with motorized system to help worker in time saving and maximum work load. Motorized wheelbarrow moves with the engine using pulley concept and gear ratio. As the results, motorized wheelbarrow 70% faster in time saving compare to manual wheelbarrow while motorized wheelbarrow 90% faster in time saving compare to manpower. Its shows that motorized wheelbarrow better in time saving compare to existing wheelbarrow in market.